Flush characteristics of several cocoa genotypes different in resistant to vascular streak dieback - Sari, Indah Anita; Setyawan, Bayu; Wahyu Susilo, Agung; Fitri Isnaini, Nurhadini; Paputpungan, Samsul; Nur’aini, Febrilia; Solecha Ruseani, Nur (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2022)
Vascular streak dieback (VSD) is one of the main diseases on cocoa that can cause a decrease in production and even death on susceptible plants. The use of selection criteria is very important in the selection process at the seedling phase, young plants and even mature plants in order to support the breeding process of resistant varieties. The aim of the study was to determine the characteristics of flush including flush color, stomata characters and duration of flush color change to green or towards mature leaves as one of the selection indicators for VSD resistance in cocoa. The research was conducted at Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute, Jember, Indonesia. Study of flush color and stomata characters was conducted using a randomized complete block design consisting of four cocoa genotypes with different levels of resistance, classified as resistant to VSD disease (Sulawesi 1, PNT 16) and as susceptible (BCL and BL 50). Each clone was repeated three times and each replication consisted of three plant samples. Flush color duration study was carried out on six cocoa genotypes as treatments, three genotypes with resistant to VSD (PNT 16, Scavina 12, Sulawesi 1) and three genotypes as susceptible to VSD (BL 50, BCL, Criollo 22). Each treatment was repeated three times and each replication consisted of three plant samples. The results showed that the resistant genotypes showed a tendency to have lower chlorophyll and anthocyanin content than the susceptible ones. The stomata character in the resistant genotypes was not different than the susceptible ones, however, the resistant genotype showed that the stomata density at flush tended to be lower. The duration of flush color change to mature leaves (green) in resistant genotypes was significantly faster than susceptible genotypes.